2022
DOI: 10.1007/s11144-022-02168-z
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading bio-based acetone to diacetone alcohol by aldol reaction using Amberlyst A26-OH as catalyst

Abstract: The aldol reaction of bio acetone in presence of a strongly basic ion exchange resin was carried out with and without the addition of water in a temperature range between − 30 °C and 45 °C. The conversion, selectivity and service time of the ion exchange resins were investigated in a stirred batch reactor and a continuous fixed bed reactor. For the batch experiments, both conversion and selectivity increased with decreasing temperature. Furthermore, the addition of water to the reaction medium has a positive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…To alternatively produce renewable products from isophorone, bio-based acetone is used for the manufacturing of Encyclopedia 2023, 3 227 isophorone [1]. The production of bio-based acetone is carried out through fermentation, e.g., the acetone-butanol-ethanol (ABE) fermentation [97][98][99][100].…”
Section: Applications and Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…To alternatively produce renewable products from isophorone, bio-based acetone is used for the manufacturing of Encyclopedia 2023, 3 227 isophorone [1]. The production of bio-based acetone is carried out through fermentation, e.g., the acetone-butanol-ethanol (ABE) fermentation [97][98][99][100].…”
Section: Applications and Synthesismentioning
confidence: 99%
“…The acetone condensation has a complex reaction mechanism with multiple possible reaction products, including mesityl oxide, phorone, mesitylene, isoxylitones, and ketonic resins [5,99,[109][110][111][112]. In 1989, Salvapati et al described the three-step reaction mechanism of acetone to isophorone shown in Figure 2 as the most likely reaction mechanism for the formation of isophorone [5].…”
Section: Applications and Synthesismentioning
confidence: 99%
See 3 more Smart Citations